13-2+2x=x+3

Simple and best practice solution for 13-2+2x=x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-2+2x=x+3 equation:


Simplifying
13 + -2 + 2x = x + 3

Combine like terms: 13 + -2 = 11
11 + 2x = x + 3

Reorder the terms:
11 + 2x = 3 + x

Solving
11 + 2x = 3 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
11 + 2x + -1x = 3 + x + -1x

Combine like terms: 2x + -1x = 1x
11 + 1x = 3 + x + -1x

Combine like terms: x + -1x = 0
11 + 1x = 3 + 0
11 + 1x = 3

Add '-11' to each side of the equation.
11 + -11 + 1x = 3 + -11

Combine like terms: 11 + -11 = 0
0 + 1x = 3 + -11
1x = 3 + -11

Combine like terms: 3 + -11 = -8
1x = -8

Divide each side by '1'.
x = -8

Simplifying
x = -8

See similar equations:

| 1.25d+3.25=1+2.25d | | x(3.5)=2.5 | | -5(-9-6)=15 | | 2.3=1/2y | | x^2+6x=573 | | -4x-18=-30 | | x^2+6x=5743 | | 6x-2(3x-5)=154 | | -66y-45x+10(7-123x)=1520 | | 2x^2+8x+x+9=0 | | 40+8x=8*5+8*x | | 8x+10=10x-5 | | 7z+5+9=-16 | | 5n^2+12n-5=0 | | x/9=43 | | d^2+30d+216=0 | | -80=10(k-8) | | 3(2+6b)=30 | | P/d-b/p=1 | | 4/9x=1*6 | | X^2+5y=19 | | C=20m+50 | | -5(2c+8)=24+4c | | 1x1/100 | | -9(v+4)+4v+7=8v+8 | | d=ux-kx | | 22=3+9(x+5) | | b=2mx+11x+1 | | 12a=28/(2/3) | | 6=r/2 | | -10(5x-9)+10x-3x=100 | | 25b-10= |

Equations solver categories